2003
DOI: 10.1152/ajpcell.00205.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A radiation transiently disrupts gap junctional communication in human keratinocytes

Abstract: 2002.-Ultraviolet A (UVA) (320-400 nm) radiation is known to cause cutaneous aging and skin cancer. We studied the effect of UVA (365 nm) radiation on the human epidermis by focusing on keratinocyte gap junction-mediated intercellular communication (GJIC). We observed a dose-dependent 10-fold decrease in GJIC induced by UVA in normal human keratinocytes. This decrease in GJIC was associated with time-dependent internalization of connexin43 (Cx43). UVA radiation also damaged the actin cytoskeleton, as shown by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…We also demonstrated that this UVA-induced reduction was reversible at a dose of 10 J/cm 2 . Our findings are consistent with previous studies (20). Inhibition of GJIc by UVA-irradiation has been reported to be associated with the deleterious effects of UVA on the human epidermis by generating ROS and compromising membrane stability (19).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We also demonstrated that this UVA-induced reduction was reversible at a dose of 10 J/cm 2 . Our findings are consistent with previous studies (20). Inhibition of GJIc by UVA-irradiation has been reported to be associated with the deleterious effects of UVA on the human epidermis by generating ROS and compromising membrane stability (19).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that GJIc is a novel UVA target, and UVA-irradiation can disrupt the function of GJIc in human keratinocytes via p38 MAPK activation (19,20). UVA can induce various pathological changes in the lens epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations